(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Zinc (Zn) is among the vital micronutrients fundamental for the growth as well as the development of humans. About 400 million people, mainly pregnant and children, go through Zn deficiency syndromes in sub-Saharan Africa. Though rice is the predominant crop in sub-Saharan Africa and a significant source of energy and micronutrients it does not supply sufficient zinc (Zn) equivalent to peoples dietary needs; rice biofortification has been recognized to be among the plants that need urgent attention to raise Zn concentration. Breeding new rice cultivars with high Zn regarded as a sustainable, cost-effective strategy to ameliorate Zn insufficiency. Agronomic biofortification alone can not solve this problem, but a synergy of agronomic biofortification and genetic approach will be more efficient. Substantial advancement has made toward increasing high Zn rice lines intended for needed countries. That will provide a relatively cost-effective, sustainable, as well as a long-term way of eradicating micronutrients to rural dwellers, the main bottleneck for rice Zn biofortification are well-known, as small transport and Zn uptake, into the grain. Extensively grain Zn accumulation should be explored. Finally, we talk about the tactical usage of Zn fertilizer meant for emergent of biofortified rice.